Factors associated with blood pressure disorders in Afro-descendant children and adolescents - Fernando Rodrigues Peixoto Quaresma; Erika da Silva Maciel; Francisco Winter dos Santos Figueiredo; Fernando Adami (BMC, 2019)
Abstract Background Hypertension (AH) is an emerging disease that has rapidly increased in the last decades throughout the world. The increase in blood pressure (BP) is observed with growth and development and, although the manifestation of the disease is rare in childhood and adolescence, its occurrence is increasing and the causes are likely to be from different combinations of factors. Afrodescendants have been consistently observed in many populations, including Brazil, which has the largest population of Afrodescendants outside Africa; nevertheless, data is scarce on the disease in children and adolescents. In this study, we investigated BP disorders in children and adolescents of "Quilombola" populations of the state of Tocantins, northern Brazil, and determined the disease occurrence with some factors, namely food consumption, body composition, anthropometric measures, and biochemical data. Methods We carried out a cross-sectional study with 67 children aged 10-17 years, comparing the variables studied between the normotensive and non-normotensive groups, using the Chi-square test for qualitative variables and the appropriate tests, according to data adherence to the Gaussian distribution for the quantitative variables. High blood pressure was defined as mean systolic or diastolic blood pressure ≥ 90 percentile for age, height, gender. Results The rate of adolescents with BP disorders was 19.4% (prehypertension 14.9% and hypertension 4.5%). There were no significant differences between the sexes for high blood pressure. In the Poisson regression analysis, the high fat percentage was associated with elevated blood pressure (p = 0.021) for adolescents. Similar associations were observed for non-HDL-c (p < 0.001) and low calcium intake (p = 0.015). Conclusion Most children and adolescents in "Quilombola" communities had normal blood pressure. However, higher levels of dyslipidemia and low calcium intake are factors associated with prehypertension in the population studied with high BP.